Rectal Dieulafoy Lesion Managed by Hemostatic Clips - Kim, Hyung Hun (Elmer Press, 2012)
The classic Dieulafoy lesion is a minute gastric mucosal defect which bleeds massively from an exposed artery. The typical endoscopic appearance of this lesion is a single, round mucosal defect with an artery protruding from its base in the absence of surrounding ulceration. We encountered an 89-year-old man who developed sudden massive fresh rectal bleeding. The source of hemorrhage was found at colonoscopy after careful irrigation and inspection to be a Dieulafoy lesion situated in rectum. Hemostasis was achieved successfully with epinephrine injection and endoscopic hemostatic clipping.